Urgensi Pengesahan RUU PKS sebagai Upaya Perlindungan Hukum Bagi Korban Revenge Porn - Kang, Cindy (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2021)
Based on data obtained from the Annual Records of the National Commission on Women, the percentage of violence against women has increased by 792% in the past 12 years. In addition, cases of Online Gender Based Violence (OGBV) have increased 300% and the most cases are revenge porn cases. This proves that women are one of the most vulnerable subjects to become victims of violence, and violence against women is not only carried out in the real world but also in cyberspace. One of the most common OGBV cases is revenge porn, where a perpetrator threatens to spread pornographic content belonging to the victim online without the victim’s consent with the potential to damage the victim’s reputation. The absence of regulations governing revenge porn makes it difficult for victims to get legal protection. The existence of the Draft Law on the Elimination of Sexual Violence (RUU PKS) which specifically regulates the types of sexual violence has given rise to hope for victims in seeking justice. The purpose of this study is to examine the urgency of the ratification of the RUU PKS regardless of the pros and cons circulating in society in providing legal protection for the victims. This study uses a normative legal research method that emphasized data obtained indirectly, such as legal materials. The results of this study indicate that the existence of laws and regulations such as the Electronic Transaction and Information Act, the Pornography Law, as well as provisions in the Criminal Code are considered insufficient to provide legal protection for the victims. Therefore, it is necessary to ratify the RUU PKS as a legal umbrella to provide protection for the victims.